USAHATANI KENTANG DENGAN TEKNIK KONSERVASI TERAS BANGKU DI DATARAN TINGGI DIENG KABUPATEN WONOSOBO JAWA TENGAH ( POTATO FARMING USING BENCH TERRACE TECHNIQUE AT DIENG HIGHLAND WONOSOBO REGENCY CENTRAL JAVA) - S., Kusmantoro Edy (Pembangunan Pedesaan, 2010)
The aims of this research were to 1) compare the potato farming productivity applying bench terrace technique of both A and B types, 2) know the effect of factors influencing the productivity and efficiency of the technique, and 3) analyze financially farmer cost and benefit of the farming. The research was conducted in Dieng Highland, Wonosobo Regrency. The primary data were taken from potato farmer in Kejajar Sub district, Wonosobo Regency, by Proportionate Stratified Random Sampling consisted of three village samples and 203 respondents. The secondary data (supporting data) were taken from related institution. Result of the research showed that the use of seeds, labors, chemical and organic fertilizers, and pesticide in the farming applying the technique of A type was higher than B type. The highest potato production was yielded in the technique of A type at three planting seasons. The factors influencing the productivity were land area, seeds, labors, chemical and organic fertilizers, pesticide cost, farmersâ age, the farming duration, the house hold members, and farmerâs education. The farming using the technique strengthened by stones was more effisience than the technique without stones. The highest benefit of the farming was found in the wet season at the land using conservation technique of A type terrace. The highest cost production was found in the wet season at the land using conservation technique of A type terrace. The potato farming in Dieng Highland was financially profitable.